Conduits for Right Ventricular Outflow Tract Reconstruction in Infants and Young Children - Qian, Tao; Yuan, Haoyong; Chen, Chunyang; Liu, Yuhong; Lu, Ting; Huang, Can; Wu, Zhongshi (Frontiers in Surgery, 2021)
Purpose of Review: Right ventricular outflow tract (RVOT) reconstruction remains a challenge due to the lack of ideal conduit. Data and experience is accumulating with each passing day. Therefore, it is necessary to review this topic from time to time. This is a 2021 update review focused on the history evolution and current situation of small-sized conduit (≤ 16 mm) for RVOT reconstruction in infants and young children. Recent Findings: Currently, the available small-sized (≤ 16 mm) conduits can meet most of the clinical needs. Homograft is still a reliable choice for infants and young children validated by half-century clinical experience. As an alternative material, bovine jugular vein conduit (BJVC) has at least comparable durability with that of homograft. The performance of expanded polytetrafluoroethylene (ePTFE) is amazing in RVOT position according to limited published data. The past century has witnessed much progresses in the materials for RVOT reconstruction. However, lack of growth potential is the dilemma for small-sized conduits. Tissue-engineering based on cell-free scaffolds is the most promising technology to obtain the ideal conduit. Summary: No conduit has proved lifelong durability in RVOT position. We are remote from the ideal, but we are not in a state of emergency. In-depth clinical research as well as innovation in material science are needed to help improve the durability of the conduits using in infants and young children.